Identity and Self-Other Differentiation in Work and Giving Behaviors: Experimental Evidence - Avner Ben-Ner; Brian P. McCall; Massoud Stephane; Hua Wang (Fondazione Eni Enrico Mattei (FEEM), 2006)
We show that the distinction between Self and Other, us and them, or in-group and out-group, affects significantly economic and social behavior. In a series of experiments with approximately 200 Midwestern students as our subjects, we found that they favor those who are similar to them on any of a wide range of categories of identity over those who are not like them. Whereas family and kinship are the most powerful source of identity in our sample, all 13 potential sources of identity in our experiments affect behavior. We explored individuals willingness to give money to imaginary people, using a dictator game setup with hypothetical money. Our experiments with hypothetical money generate essentially identical data to our experiments with actual money. We also investigated individuals willingness to share an office with, commute with, and work on a critical project critical to their advancement with individuals who are similar to themselves (Self) along a particular identity dimension than with individuals who are dissimilar (Other). In addition to family, our data point to other important sources of identity such as political views, religion, sports-team loyalty, and music preferences, followed by television-viewing habits, dress type preferences, birth order, body type, socio-economic status and gender. The importance of the source of identity varies with the type of behavior under consideration.
Keywords: 330; Identify; Diversity; Experimental Economics; Conflict; Persönlichkeitspsychologie; Test; Industriesoziologie